2020
DOI: 10.1515/eng-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Strength Analysis of S34MnV Steel by Accelerated Staircase Test

Abstract: AbstractThis paper presents the reliability estimation of fatigue strength of the material used for crank throw components. The material used for crank throw components is forged S34MnV steel and subsequently heat-treated by normalising and tempering. High cycle fatigue testing under fully reversed cycling (R = −1) was performed to determine the fatigue limit of the material. The staircase test method is used to obtain accurate values of the mean fatigue limit stress until a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This fatigue test method has been widely accepted to examine the fatigue limit of metals. There were also some modified staircase procedures to reduce the number of test specimens and hence lower the cost and running time of this test [26][27].…”
Section: Fatigue Testmentioning
confidence: 99%
“…This fatigue test method has been widely accepted to examine the fatigue limit of metals. There were also some modified staircase procedures to reduce the number of test specimens and hence lower the cost and running time of this test [26][27].…”
Section: Fatigue Testmentioning
confidence: 99%
“…Fatigue limit, usually expressed as a stress amplitude, is defined as a fatigue strength below which the component has an infinite fatigue life, [1] and it can be used as a reference value to obtain an estimation of the fatigue state. In practice, the limit value is hard to be determined accurately, and normally it is considered as the fatigue strength which displays at typically 10 6 − 10 7 load cycles [2–5] . Therefore, the fatigue limit is located between high cycle fatigue and unlimited endurance domain, and it needs to be identified by the experimental fatigue test.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the limit value is hard to be determined accurately, and normally it is considered as the fatigue strength which displays at typically 10 6 À 10 7 load cycles. [2][3][4][5] Therefore, the fatigue limit is located between high cycle fatigue and unlimited endurance domain, and it needs to be identified by the experimental fatigue test.…”
Section: Introductionmentioning
confidence: 99%
“…However, fatigue testing is costly and time-consuming. Literature studies revealed that the staircase, as an accelerated fatigue testing method, can accurately estimate the fatigue strength in a reasonable time (Ekaputra et al 2020;Wallin 2011). PSA currently uses staircase-Locati procedures for fatigue testing of critical parts like engine mounting brackets (Beaumont et al 2012).…”
Section: Introductionmentioning
confidence: 99%